Étude lexicométrique des termes centraux dans un corpus d’articles scientifiques en orthophonie - Frédérique Brin-Henry; Évelyne Jacquey; Sandrine Ollinger (Lexis: Journal in English Lexicology)
We have been studying the professional and scientific discourse of speech and language therapists (SLTs) for more than ten years. One of our projects currently focuses on the identification of what we will refer to as central terms among French speech therapists. These lexical units are used in a particular way by SLTs. They may be considered as very typical in that they tend to contribute to the characterisation of SLT practice. The aim of our study is first to establish a reproducible method for selecting terms that are useful for the characterisation of SLT practice, and then to contribute to the definition of its terminology.A list of 21 lexical units was drawn up by one of the authors (who is also a SLT), and submitted to a panel of other SLT experts. Concurrently, we developed a corpus-based method in order to identify and describe the use of central terms in SLT discourse. Usual analyses on concordances were conducted, as well as frequency measures and examination of regular expressions. We used a corpus built during the OrthoCorpus project. The corpus contains 850 scientific articles which were published between 1997 and 2014 in the French SLT journal entitled Rééducation Orthophonique.In this article, we describe each additional step we took and the results we found for eight of the examined lexical units. Our results are consistent for four units. We then conclude on the consequences these results may have on the future of our work.